A comparative analysis of engine characteristics from various biodiesels: Numerical study. (15th January 2019) - Rajak, Upendra; Verma, Tikendra Nath
Graphical abstract: Highlights: Simulation carried out of edible and non-edible oil, waste fats, waste oil and alcohol. SFC of biodiesels were higher than those of diesel fuel. Combustion duration of biodiesels is lower than diesel. The proposed tool can be used to simulate parameters of CI engine. Abstract: The present study involves the numerical simulation of the diesel engine by means of Diesel-RK, tool for determining engine characteristics for diesel, vegetable oil, animal fats, waste oils and alcohols respectively. Simulation results are verified with experimental results and exhibits a good agreement for diesel fuel. The tool also delivers a reasonably accurate prediction of in-cylinder pressure, in-cylinder heat rate, and fuel consumption in combustion and NOX emission level. The study shows maximum power and cylinder peak pressure obtained were of 17.65% for coconut oil and 1.5%, 0.77%, 2.3%, and 17.8% for rapeseed oil, fish oil and veal oil, waste frying oil and propanol biodiesel respectively. On the other hand, the ignition delay was found to be lower than diesel for biodiesel and even decreased with an increase in engine load. The combustion duration obtained to be higher for biodiesels compared to diesel fuel. Simulation results are conducted under different engine loads, constant speed (1500 rpm) and advanced injection timing 23.0° b TDC with higher injection pressure.